Age, growth and population structure of the yellowfin tuna Thunnus albacares (Bonnaterre, 1788) exploited along the east coast of India - Rohit, Prathibha; Syda Rao, G.; Rammohan, K. (Indian Journal of Fisheries, 2025)
Lengths measurements of 6,758 yellowfin tuna (Thunnus albacares), landed by hook and line operators off eastern Indian coast were taken (20â€“185 cm FL) from 2003 to 2009. Age and growth were estimated using length based methods. The von Bertalanffy growth parameters estimated were Lâˆ = 197.42 cm, annual K= 0.30 and t0= -0.1157. Mortality estimates were M= 0.48 and Z= 0.71 and F= 0.23 with the exploitation ratio E= 0.32. Growth was rapid during the initial years when the annual growth increment was as high as 36.6 cm during the first year then which to as low as 3.3 cm in the tenth year. The fish attained a fork length of 56.2 cm at the end of one year. Size at maturity (87.5 cm) corresponded to an age of 1.7 years and the oldest individual in the sample was 9+ years (186 cm). The annual mean lengths varied from 80.6 cm to 115.3 cm with an average mean length of 101.9 cm. The fishery comprised of mostly adults with 64% comprising of fishes larger than size at first maturity.